Persepsi kegunaan dan kemudahan terhadap intensitas penggunaan mobile banking: Studi PT Bank Sulutgo Cabang Utama Manado - Christina Mikhaila Suoth; Hendrik Gamaliel; Claudia W.M. Korompis (Manajemen Bisnis dan Keuangan Korporat, 2026)
This study aims to examine the effect of perceived usefulness and perceived ease of use on the intensity of Mobile Banking usage among customers of PT Bank Sulutgo Main Branch Manado, a regionally owned bank (BUMD) facing increasing pressure to digitalize its services. Grounded in the Technology Acceptance Model (TAM), the study employed a quantitative associative approach. Data were collected through Likert-scale questionnaires distributed to 383 respondents drawn from a population of 9,100 Mobile Banking users, with the sample size determined using the Slovin formula at a 5% margin of error. Data were analyzed using multiple linear regression with SPSS. The results show that, partially, perceived usefulness has a positive and significant effect on usage intensity (t = 10.616; p < 0.001), as does perceived ease of use (t = 7.413; p < 0.001). Simultaneously, both variables significantly affect usage intensity (F = 413.086; p < 0.001). The Adjusted R² of 0.683 indicates that perceived usefulness and perceived ease of use explain 68.3% of the variation in Mobile Banking usage intensity, while the remaining 31.7% is explained by other factors outside the model, such as security, trust, service quality, and perceived risk. These findings confirm that both cognitive-benefit and effort-related perceptions jointly drive digital-banking adoption behavior in a regional banking context.